Case Report: A rare case of unilateral renal clear cell carcinoma with synchronous contralateral ureteral metastasis - Qian, Yichen; Lu, Yuanchen; Zhang, Qijie; Xie, Jianjun; Shen, Hua; Deng, Junpeng (Frontiers in Oncology, 2026)
BackgroundRenal cell carcinoma (RCC) rarely metastasizes to the contralateral ureter. Fewer than 10 such cases have been reported, mostly involving clear cell RCC (CCRCC) with associated hydronephrosis and renal insufficiency. The mechanism may involve retrograde tumor cell implantation via the urine. This report presents a rare case of unilateral CCRCC with synchronous contralateral ureteral metastasis and its treatment.Case presentationA 77-year-old male patient presented with hematuria and right lumbar pain. Computed tomography (CT) imaging revealed a left renal mass and a small right ureteral mass with hydronephrosis and suggested malignancy in both masses. Owing to bilateral involvement and poor general condition, a staged approach was adopted. Laparoscopic partial nephrectomy of the left renal mass yielded clear cell renal cell carcinoma (CCRCC). Subsequent laparoscopic nephroureterectomy for the right ureteral tumor confirmed CCRCC metastasis. The patient recovered well and showed no metastasis at the fourteen-month follow-up.ConclusionThis type of metastasis deserves increased attention. However, there is currently no standardized treatment protocol for this rare condition. Our treatment involved firstly management of the renal tumor, followed by the contralateral ureteral tumor so that optimal safety and minimum oncological progression can be achieved.